Antecedents and Consequences of Credibility and Parasocial Interaction on Food Shopping Intentions - Dea Farahdiba (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: In recent years, vlogging or a trending term, especially among YouTube viewers, has increasingly bombarded content on Google's video site. This study examines the antecedents and consequences of credibility and parasocial interactions on food shopping intentions. Design/Methods/Approach: The data was obtained through a survey of 117 followers of one of the five favorite food vlogger accounts of the Indonesian people based on a survey conducted by CNBC Indonesia (2020) and who have shopped for food products at least three times in the last six months. Data analysis is performed using the Structural Equation Model- Partial Least Square (SEM-PLS) to test the suitability of the hypothesized model. Findings: The findings of this study suggest that food stall owners can consider choosing celebrities or ambassadors to have their products reviewed to attract wider consumers. Originality: This study explores the attractiveness of celebrities on social media, especially YouTube, which can influence the purchase intention of their followers and the role of parasocial interaction and credibility in these interactions and results. Practical/Policy implication: The results of this study indicate that company management pays attention to who is right to promote their products. Influencers who will be used as promotional materials must also be in line with the products produced by the company so that there is no mistake in getting a wider consumer.